Gymnastic Exercises for Physical Preparation in Production Facilities - Xasanova Saboxat Ilhom qizi; Ма`murova Kamola Komiljon qizi; Xolmaxmatov Boburjon Musurmon òģli; Kenjayev Dilshod G'ayrat o'g'li (International Journal on Orange Technologies, 2021)
In the article, industrial enterprises carry out a constant stream of physical culture and sports, especially gymnastics exercise complexes 2-3 percent is an increase in performance at the same time to perform complex gymnastic exercises and physical training complexes about those moments.